THE DEVELOPMENT OF ART EDUCATION IN LATVIA FROM 1890 TILL 1990 - Muze, Agata (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
Art education is a very important field, as it represents the ethical and esthetical needs of the society and reflects the politics and ideology of the age. The urgency of art education and cultural education is affirmed also by the fact that the year 2009 was announced as the year of innovations and creativity in Europe. It is necessary to research the possibilities the art education can offer to promote the creativity of young people and to improve the quality of art education. The overview of the history of art education gives us the possibility to find connections between different conditions as well as examples of the best practice. The development of art education is divided into three stages within the period from 1890 to 1990: founding of the first establishments of art education at the end of the 19th century (1890 – 1915), development and growth of the establishments of art education during the independence period in Latvia (1915 – 1940) and changes brought by the time of occupation (1940 – 1990). This period shows the development of art education in three different contexts of social, economical and political ideology, giving us the opportunity to see their influence on the development of the cultural and spiritual life of Latvians. The aim of the research: to gather and analyze the main tendencies of the development of art education from 1890 to 1990. Methods of research: analysis of the scientific literature and sources.